Identification of pathogenic bacteria from infected Thai koi (Anabas testudineus) - Chhanda, Mousumi Sarker; Parvez, Imran; Rumi, Nazmi Ara; Hosen, Md Hafiz All; Islam, Md Rezaul (Asian Journal of Medical and Biological Research, 2019)
A study was conducted for identification of pathogenic bacteria from Thai koi (Anabas testudineus) and an experimental infection test was run for identifying the actual causative agent of the infection. Due to perform the experiment, the fish sample was collected from different fish farm located in Fulbari, Dinajpur to the Microbiology lab of the HSTU-Dnajpur campus and placed in tray for taking sample from different infected part such as gill, slime, muscle, fin of the fish by using wire loop then these were taking in the nutrient ager medium for observing the culture of bacteria. After then specific culture media, Salmonella-Shigella media, Mannitol salt agar media, Mac-Conkey (MaC) agar media and Eosin Methylene Blue media were used for observing specific bacterial characteristics. Then biochemical tests, Methyl red (MR), Voges-proskaure test, Triple sugar iron test, Indole test were performed for bacterial identification. As a result Salmonella spp., Shigella spp., Klebshiella spp. and Staphylococcus spp. were confirmed. Catalase test and Simon citrate test was also performed. Then Grams staining method was followed for microscopic observation of identified bacteria. Then experimental infection test was performed in Aquaculture lab by setting up 5 aquarium holding fresh fish. The fresh water and identified bacteria were added specifically to the aquarium and it was continued for 15 days for observing infectious symptoms. After 15 days the fish with Salmonella spp. and Staphylococcus spp. were showed infectious symptoms but other did not any change in physical appearance. So it can be said that Staphylococcus spp. and Salmonella spp. are able to show ulcerative symptoms in Thai koi (Anabas testudineus) that is a bacterial infection. Asian J. Med. Biol. Res. March 2019, 5(1): 56-62